Sosialisasi Pemahaman Anak dalam Memilih Sekolah Bagi Guru dan Orang Tua Siswa di UPTD SDN 6 Nagri Kaler - Idat Muqodas; Nur Fitri Lailatul Hasanah; Ramanda Ayang Rutanti; Rina Kurniawati; Sri Mulyati; Wahida Kusuma Wijareni; Yogie Maulana Ikhbal (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
Understanding in choosing the right school for children is important; this can influence children's learning motivation and develop children's interests and potential. This service activity aims to provide understanding to children about the importance of choosing the right school. Implementing this service activity is carried out online through Zoom and offline, which is carried out in schools according to health protocols. The implementation of this service activity is carried out in three stages, namely 1) the preparation stage, 2) the core stage 3) the evaluation stage. There is great hope that after this socialization, children can determine their choice of school according to their potential, interests, and talents while still considering suggestions from parents.